2021
DOI: 10.2196/18834
|View full text |Cite
|
Sign up to set email alerts
|

User Engagement With Smartphone Apps and Cardiovascular Disease Risk Factor Outcomes: Systematic Review

Abstract: Background The use of mobile health (mHealth) interventions, including smartphone apps, for the prevention of cardiovascular disease (CVD) has demonstrated mixed results for obesity, hypercholesterolemia, diabetes, and hypertension management. A major factor attributing to the variation in mHealth study results may be mHealth user engagement. Objective This systematic review aims to determine if user engagement with smartphone apps for the prevention an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
4
33
1
Order By: Relevance
“…Our findings corroborate past work that found significant associations between the frequency of food logging and weigh-ins and weight loss outcomes [ 10 , 17 - 22 ]. Departing from some past studies, we found that weight loss outcomes were associated with all engagement measures over all time periods, with one exception.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings corroborate past work that found significant associations between the frequency of food logging and weigh-ins and weight loss outcomes [ 10 , 17 - 22 ]. Departing from some past studies, we found that weight loss outcomes were associated with all engagement measures over all time periods, with one exception.…”
Section: Discussionsupporting
confidence: 92%
“…Previous work has found positive associations between engagement and weight loss outcomes [ 10 , 17 - 22 ]. In a digital commercial program, the number of weigh-ins per week, steps per day, active minutes per week, days logging meals per week, and the percentage of weeks with 5 or more meal logs were associated with weight loss at 6 months [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical data processing is an important aspect that several wearable device manufacturers have addressed through a cloud storage scheme, where specialized applications can later query the data. Furthermore, literature reviews on cardiovascular diseases [ 128 , 129 , 130 , 131 , 132 , 133 ] and diabetes [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] have described apps designed for specific diseases that were not addressed here, as they were outside the scope of this research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, conversational agents that use artificial intelligence to proactively guide, prompt, and check in with participants and encourage general use of the app have been found to improve the therapeutic alliance between the participant and the intervention, resulting in more engagement [ 36 ]. In other studies, the ability to set goals, self-monitor progress, and receive feedback increased engagement across a variety of health behaviors, including alcohol use [ 37 ]. An advantage of apps is their ability to generate utilization data, which are commonly used as a proxy for quantifying engagement.…”
Section: Introductionmentioning
confidence: 99%